Develop Human Integrity and Quality through Lecturing Management Control Systems - Susilawati, Wati; Turipanam Alamanda, Dini; Muhamad Ramdani, Risma; Sidiq Adi Prabowo, Fajar; Ramdhani, Abdullah (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to identify students’ responses on the issue of management control of lecturing activities in Indonesia through discussion of case studies. The concept of management control becomes the topic of discussion in the focus group discussion (FGD) conducted during the Management Control System course at Garut University. The FGD was conducted for 150 minutes involving 10 students. The participants are from various student organizations and have different experiences in the organization. The FGD focused on the syllabus of Management Control System courses for students in the third level. The results of the FGDs showed that some materials of the Management Control System (MCS) course encouraged the students to have integrity. The materials covered management and control, planning and budgeting, and comprehensive management control. The discussion and recommendation for this course syllabus are elaborated comprehensively.